Review articleMore light on the practical problems of the metabolic syndrome - Tatoń, Jan; Czech, Anna; Bernas, Małgorzata; Rubiec-Niemirowska, Anna (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2006)
The definition of the metabolic syndrome was established primarily on the basis of clinical observations. The aetiopathogenetic interpretation of the cluster of symptoms and disturbances called metabolic syndrome is actually not possible. This is the cause of changing and modifying the definitions as presented by different groups of experts. This cognitive impact makes the diagnostics, prevention and therapy of this syndrome difficult. It seems that actually, in cases of metabolic syndrome – full or partial – the determination of the resistance to insulin is mandatory. Respectively to the primary preventive and therapeutic interventions should be directed toward decreasing the resistance to insulin – also pharmacologically. With this therapy the symptomatic interventions could be combined in the form of multifactorial management, decreasing the risk of atherosclerosis. Further data in this area are very much needed.